Study of Causal Relationship between the Gross Domestic Product and the Profitability of Islamic Banks An Applied Study on Islamic Banks in Syria (Journal of Hama University, 2021)
This study aimed to identify the nature of the causal relationship between the gross domestic product and the profitability of private Islamic banks in Syria, which was measured by the rate of return on property rights during the period 2010-2017, based on the annual financial statements of Islamic banks published in the Damascus Stock Exchange, as well as The descriptive approach was based on the use of statistical methods of cross-sectional time data, where the stability of time series was studied and a causation test was conducted for Granger between GDP and the profitability of Islamic banks using Eviews program. The study found a one-way causal relationship from profitability to GDP.